Accounting and Auditing Decisions in Family Firms: A Review within the Context of Family Capitalism (Third Sector Social Economic Review, 2026)
Family firms are hybrid organizations that consolidate the distinct economic motivations of the family and the firm under a single roof. Strategic decision-making in these firms is shaped by a continuous tension between objective economic imperatives and socio-emotional wealth (SEW) considerations-including preserving family reputation, maintaining long-term control, and ensuring successful transgenerational succession. Such socio-emotional dynamics directly influence critical financial processes, including financial reporting quality, auditing, and risk management strategies. The primary objective of this study is to provide an integrative analysis of family firms' management, accounting, and auditing, framed by agency theory and the socio-emotional wealth hypothesis. Moving beyond the type 1 agency problems typical of dispersed ownership structures, this research emphasizes the family capitalism model and type 2 agency conflicts prevalent in emerging markets like Türkiye. Within the Turkish context, concentrated ownership and complex pyramidal structures represent significant structural barriers to financial transparency and capital market liquidity. By synthesizing current literature, the study identifies critical research gaps regarding the impact of family capitalism on financial decision-making. Ultimately, the findings establish a theoretical foundation for future researcher and offer practical recommendations to enhance institutionalization and audit quality in environments characterized by concentrated ownership.
Keywords: Family Firms; Family Capitalism; Type 2 Agency Theory; Financial Reporting Quality; Socio-Emotional Wealth (SEW)